Preface - Fuchs, Christian (Yuqi Na: The Chinese Internet. Political Economy and Digital Discourse)

Grundlagen einer Ethik des Radikalen Digitalen Humanismus - Fuchs, Christian (Digitalisierte Massenkommunikation und Verantwortung)

Vincent Mosco’s Critical-Humanist Political Economy of Communication - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Critical Perspectives on Digital Capitalism: Theories and Praxis (tripleC: Communication, Capitalism & Critique)

Critical Theory Foundations of Digital Capitalism: A Critical Political Economy Perspective - Fuchs, Christian (tripleC: Communication, Capitalism & Critique.)

Critical Perspectives on Digital Capitalism: Theories and Praxis. Introduction to the Special Issue - Fuchs, Christian; Arslan, Sevda Can; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens: Theorie, Methodik und Einblicke in die Vergänglichkeit)

Digital Ethics. Media, Communication and Society Volume Five - Fuchs, Christian

Der digitale Kapitalismus. Arbeit, Entfremdung und Ideologie im Informationszeitalter - Fuchs, Christian

Adorno and the Media in Digital Capitalism - Fuchs, Christian (Adorno und die Medien: Kritik, Relevanz, Ethik)

Zur Kritik der Politischen Ökonomie des Digitalen Kapitalismus: Die Aktualität von Manfred Knoches Beitrag zur Kritik der Politischen Ökonomie der Medien und der Kommunikation - Fuchs, Christian (Eigentum, Medien, Öffentlichkeit: Verhandlungen des Netzwerks Kritische Kommunikationswissenschaft)

The Problems of Base/Superstructure and Ideology in the Works of Stuart Hall, Georg Lukács, and Raymond Williams - Fuchs, Christian (The Communication Review.)
We live in times of deep crisis. General crises of society often are accompanied by ideological struggles. Given this context, it is important that social theory reinvigorates the analysis of ideology. For doing so, it makes sense to engage with classical theories of ideology. This paper contributes to this task. It asks: How are the economic and the non-economic related? What is ideology? This article deals with the base/superstructure problem and the problem of ideology via an engagement with selected aspects of Stuart Hall’s, Georg Lukács’s and Raymond Williams’s works. The commonality of Hall’s, Lukács’s and Williams’s thoughts that makes a joint engagement with their works feasible is that they all three dealt with aspects of culture from a critical theory perspective and are in one way or another representatives of Cultural Marxism. While Lukács’s works and Cultural Studies are often presented as conflicting approaches, this paper shows that concerning the question of how the economic and the non-economic are related and how we can think of ideology, the approaches of Lukács, Williams, and Hall complement each other, which allows critical theories of culture to draw on all three approaches and to combine elements from them in a synergistic manner. There are parallels between Williams’, Hall’s, and Lukács’s solutions to the base/superstructure problem. Williams argues that the economic exerts pressures on and sets limits to the non-economic. Hall writes that the economic determines the non-economic in the first instance. Lukács argues that the economic circumscribes subjectivity and the non-economic.
Keywords: base and superstructure; culture; economy and culture; Georg Lukács; ideology; Raymond Williams; Stuart Hall

Ibn Khaldûn and the Political Economy of Communication: A Reply to Graham Murdock - Fuchs, Christian (Critical Sociology)

Ibn Khaldûn and the Political Economy of Communication in the Age of Digital Capitalism - Fuchs, Christian (Critical Sociology)

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

Grundlagen der Medienökonomie: Medien, Wirtschaft und Gesellschaft. - Fuchs, Christian

Verschwörungstheorien in der Pandemie - Fuchs, Christian

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

Digital Capitalism. Media, Communication and Society Volume Three - Fuchs, Christian

Digital Fascism. Media, Communication and Society Volume Four - Fuchs, Christian

Foundations of Critical Theory. Media, Communication and Society Volume Two - Fuchs, Christian

Marxism and Identity - Fuchs, Christian (Searching for a Self. Identity in Popular Culture, Media and Society)

Verschwörungstheorien in der Pandemie. Wie über COVID-19 im Internet kommuniziert wird - Fuchs, Christian

交往资本主义：迈向马克思主义交往理论的批判 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences))

数字资本主义和大数据时代的卢卡奇 - Fuchs, Christian (马克思主义与现实 (Marxism & Reality) 年第5期. (shortened article version))

数字、传播与社会主义 - Fuchs, Christian (国外理论动态 (Foreign Theoretical Trends))

社交媒体中的数字产消劳动：基于资本主义时间范畴的研究 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (4))

H παρακολούθηση των Κοινωνικών Μέσων - Fuchs, Christian (Η νέα ψηφιακή παρακολούθηση. Κείμενα προς τιμήν του Μηνά Σαματά (in Greek, The New Digital Surveillance: A Volume in Honour of Minas Samatas),)

Geburtstage: Manfred Knoche 80 Jahre - Fuchs, Christian (Publizistik)

Journalismus aus marxistischer Perspektive - Fuchs, Christian (Journalismustheorien)

Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens)

Occupy the Internet: Why we need a Public Service Internet - Unterberger, Klaus; Fuchs, Christian (Building a European Digital Public Space: Strategies for Taking Back Control from Big Tech Platforms)

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

大数据、社交媒体和数字异化 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (5))

Servizio Pubblico - Fuchs, Christian (Wired Italia 102)

Digital Humanism. A Philosophy for 21st Century Digital Society. SocietyNow Series - Fuchs, Christian

Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

The Public Service Media and Public Service Internet Utopias Survey Report - Fuchs, Christian (The Public Service Media and Public Service Internet Manifesto)

Communicating COVID-19. Everyday Life, Digital Capitalism, and Conspiracy Theories in Pandemic Times. SocietyNow Series - Fuchs, Christian

History and Class Consciousness 2.0: Georg Lukács in the Age of Digital Capitalism and Big Data - Fuchs, Christian (Information, Communication and Society)

Marxist Humanism and Communication Theory. Media, Communication and Society Volume One - Fuchs, Christian

Engels@200: Friedrich Engels and Digital Capitalism. How Relevant Are Engels’s Works 200 Years After His Birth? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Engels@200: Friedrich Engels in the Age of Digital Capitalism. Introduction - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Cornel West and Marxist Humanism - Fuchs, Christian (Critical Sociology)

Das digitale Kapital. Zur Kritik der politischen Ökonomie des 21. Jahrhunderts - Fuchs, Christian

The Public Service Media and Public Service Internet Manifesto

Social Media: A Critical Introduction. Third English edition - Fuchs, Christian

The Future of Public Service Media and the Internet - Alessandro, D'Arma; Fuchs, Christian; Horowitz, Minna; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

Introduction - Fuchs, Christian; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

The Digital Commons and the Digital Public Sphere: How to Advance Digital Democracy Today - Fuchs, Christian (Westminster Papers in Communication and Culture)

How Did Donald Trump Incite a Coup Attempt? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Foundations of Communication/Media/Digital (In)Justice - Fuchs, Christian (Journal of Media Ethics)

Channel 4: Rather Than Privatising Public Service Media We Should Be Expanding It Online - Fuchs, Christian (The Conversation)

数字劳动与卡尔·马克思 - Fuchs, Christian

Enformasyon Çağında Marx Okumak. Kapital Cilt 1 Üzerine Bir Medya ve İletişim Çalışması - Fuchs, Christian

Soziale Medien und kritische Theorie. Second German edition - Fuchs, Christian

Membaca Kembali Marx Di Era Kapitalisme Digital - Fuchs, Christian

Dijital Kapitalizm Çağında Marx’ı Yeniden Okumak. BeneDijital Kapitalizm Çağında Marx’ı Yeniden Okumak - Fuchs, Christian

受众商品、数字劳动之争、 马克思主义政治经济学与批判理论 (The Audience Commodity, the Digital Labour Debate, Marxist Political Economy, and Critical Theory). - Fuchs, Christian (国外社会科学前沿 (International Journal of Social Science) 2021 (4))

Dijital Nesneler, Digital Özneler - Büyük Veri Çağında Kapitalizm, Emek ve Siyaset Üzerine Disiplinlerarası Yaklaşımlar

弗洛姆与交往批判理论 - Fuchs, Christian (国外理论动态 (Foreign Theoretical Trends) 2021 (3))

Preface: Manfred Knoche’s Critique of the Political Economy of the Media and Communication [Preface to the article “Media Concentration” by Manfred Knoche] - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Engels@200: Friedrich Engels in the Age of Digital Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

卡尔·马克思与互联网研究 - Fuchs, Christian; Dyer-Witheford, Nick (国际社会科学杂志 (Journal of International Social Sciences) 2021 (9))

Communication and Capitalism. A Critical Theory - Fuchs, Christian

Marxism. Karl Marx’s Fifteen Key Concepts for Cultural and Communication Studies. Key Ideas in Media & Cultural Studies Series - Fuchs, Christian

Nationalism on the Internet: Critical Theory and Ideology in the Age of Social Media and Fake News - Fuchs, Christian

Towards a Critical Theory of Communication as Renewal and Update of Marxist Humanism in the Age of Digital Capitalism - Fuchs, Christian (Journal for the Theory of Social Behaviour)

Marx heute. Eine Einführung in die kritische Theorie der Kommunikation, der Kultur, der digitalen Medien und des Internets - Fuchs, Christian

Kommunikation und Kapitalismus. Eine kritische Theorie - Fuchs, Christian

Alltagsleben und Alltagskommunikation im Coronavirus-Kapitalismus - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Everyday Life and Everyday Communication in Coronavirus Capitalism - Fuchs, Christian (tripleC: Communication)

The Utopian Internet, Computing, Communication, and Concrete Utopias - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Erich Fromm and the Critical Theory of Communication - Fuchs, Christian (Humanity & Society)

The Ethics of the Digital Commons - Fuchs, Christian (Journal of Media Ethics)

Sosyal Medya: Eleştirel Bir Giriş - Fuchs, Christian

数字时代的资本主义、父权制、奴隶制与种族主义 - Fuchs, Christian (国外社会科学前沿 (Studies on Foreign Social Sciences))

Interview mit Christian Fuchs: »Der Sozialismus ist keine App und kann nicht aus dem Internet heruntergeladen werden«. Marx’ Vision der befreiten Gesellschaft bleibt im digitalen Zeitalter aktuell - Fuchs, Christian (Das Argument)

Vida e comunicação cotidianas no capitalism da coronavirus - Fuchs, Christian (MATRIZes)

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

罗铮 译.“大数据资本主义时代的马克思（Karl Marx in the Age of Big Data Capitalism) - Fuchs, Christian (世界社会主义研究年鉴 (World Socialism Research Yearbook 2020))

罗铮 译.“大数据资本主义时代的马克思（Karl Marx in the Age of Big Data Capitalism - Fuchs, Christian (国外理论动态（Foreign Theoretical Trends) 2020 (4))

Preface to Manfred Knoche’s Article “Science Communication and Open Access: The Critique of the Political Economy of Capitalist Academic Publishers as Ideology Critique” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Rereading Marx in the Age of Digital Capitalism - Fuchs, Christian

Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data

Henri Lefebvre’s Theory of the Production of Space and the Critical Theory of Communication - Fuchs, Christian (Communication Theory)

Öffentlichkeit im digitalen Kapitalismus - Fuchs, Christian (Das Ende der Vielfalt? Zur Diversität der Medien)

Social Media, Big Data, and Critical Marketing - Fuchs, Christian (The Routledge Companion to Critical Marketing)

Appropriation of Digital Machines and Appropriation of Fixed Capital as the Real Appropriation of Social Being: Reflections on Toni Negri’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

M. N. Roy and the Frankfurt School: Socialist Humanism and the Critical Analysis of Communication, Culture, Technology, Fascism and Nationalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

What is Critical Digital Social Research? Five Reflections on the Study of Digital Society - Fuchs, Christian (Journal of Digital Social Research)

We Need a Full Public Service Internet – State-Owned Infrastructure is Just the Start - Fuchs, Christian (The Conversation)

Boris Johnson Takes His Brexit Demagoguery to the Social Media Sphere - Fuchs, Christian (TruthOut)

重读马克思:资本主义批判与激进理论的未来[J] - Fuchs, Christian; Monticelli, Lara (国外理论动态 (Foreign Theoretical Trends) 2019 (8))

Critical Theory of Communication: New Readings of Lukács, Adorno, Marcuse, Honneth and Habermas in the Age of the Internet (Chinese translation) - Fuchs, Christian

Revisiting the Althusser/E. P. Thompson-Controversy: Towards a Marxist Theory of Communication - Fuchs, Christian (Communication and the Public)

Beyond Big Data Capitalism, Towards Dialectical Digital Modernity: Reflections on David Chandler’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Introduction: Big Data Capitalism – Politics, Activism, and Theory - Fuchs, Christian; Chandler, David (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Karl Marx in the Age of Big Data Capitalism - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)